Management Practices to Support Increased Biodiversity in Managed Loblolly Pine Plantations - Michael G. Andreu; Kevin W. Zobrist; Thomas Hinckley (EDIS)
FOR-183, a 9-page fact sheet by Michael Andreu, Kevin Zobrist, and Thomas Hinckley, reviews the literature to identify a spectrum of practices that support increased biodiversity in intensively managed loblolly pine plantations. Includes references. Published by the UF School of Forest Resources and Conservation, March 2008.